MELACAK AKTIFITAS ILLEGAL FISHING MELALUI PEMANFAATAN AIS (AUTOMATIC IDENTIFICATION SYSTEM) PADA KAPAL DAN AIS HYBRID SEBAGAI ALAT BANTU PENANGKAPAN IKAN - Simau, Silvester; Prakoso, Imam; Manengkey, Jenny I; Manohas, Jul; Pontoh, Peggy; da Gomez, Grandhi K (Politeknik Kelautan dan Perikanan Bitung, 2022)
Information technology is growing rapidly with various facilities that can be obtained through various fields of work. Information technology can also be found in the field of work on fishing vessels. One of the means of communication that is being used by Indonesian commercial vessels (excluding fishing vessels) in the last two years is the Automatic Identification System (AIS). AIS is a Maritime Navigation System and Radio Communication. This system aims to improve life safety at sea, safety and efficiency of shipping and protection of the marine environment by communicating navigation information automatically on VHF channels between ships, as well as from ships and shore. Fishing technology is gradually changing in the use of fishing aids with various ease of operation. Information technology developed by prioritizing easy access to data and information in the use of fishing aids. One of the information technologies used today is the use of AIS devices in ship’s navigation and marking fishing gear that is being operated. AIS is a maritime navigation and radio communication system. This system aims to improve life safety at sea, safety and efficiency navigation as well as the protection of the marine environment by automatically communicating navigational information on the VHF channel between ships, through AtoN and shore stations. Various technological innovations developed with this AIS device have resulted in AIS hybrid that can be used as a fishing gear, especially as a fishing gear marker Fishing aids that have been used so far by fishermen in terms of marking fishing gear that are being operated are marker buoys, radio buoys supported by RDF devices. The use of AIS hybrid in fishing techniques with long lines or other fishing gear is one of the technological developments, especially the use of AIS hybrid as a tool or a marker when fishing gear is operated. The use of AIS hybrid on fishing vessels as a marker for fishing gear has not been widely applied in Indonesia. This needs to be introduced to fishermen or fishing vessel officers as has been used on foreign fishing vessels operating in Indonesian EEZ waters. In order to avoid errors in accessing AIS data in the vessels tracking lane due to the AIS hybrid, it is recommended that the AIS hybrid MMSI number be issued by the competent authority in accordance with the applicable provisions of the IMO standard.